Working memory in children with attention deficit hyperactivity disorders and their siblings - Wei, Wee Kok (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
Objective: To assess and compare working memory of ADHD children and their siblings. Method: 57 subjects were recruited: 1) ADHD group (n = 21), 2) siblings of ADHD children group (n=l5), and 3) non-ADHD children with chronic medical condition as the control group (n = 21). Digit Recall, Maze Memory Test and Backward Digit Recall were used to assess working memory. Result: ADHD children and their siblings showed similar impairment and both differed from the control group on the Mazes Memory test. ADHD children also showed impairment in Digit Recall test, however the siblings group did not differ from the control group. The score of Backward Digit Recall did not show any significant difference between the 3 groups. Conclusion: Impairment of the visuospatial sketch pad component of working memory seems to cluster in ADHD children and their siblings (from Maze Memory Test).